Czym jest dziś czytanie literatury? Ankieta - Świerkocki, Maciej (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Maciej Świerkocki notes that reading was and still is an exclusive and intellectual activity, an important part of education of a pragmatic society oriented on the acquisition of information. The author points out that reading is like slow food, as it is associated with slowness and contemplation, today — with the world of creation rather than mimetism. He links the postmodernisation of reading with postmodernisation of literature.